A novel measure to quantify technical ability in on-water rowing - Jones, S.; Bailey, C.; Thomas, D.; White, M. G. E.; Rees, P.; Summers, H. D.; Bezodis, N. E. (Journal of Sports Sciences, 2025)
This study developed a new measure that quantifies technical ability in on-water rowing by accounting for the effects of an athlete`s physiological capabilities and the given environmental conditions. Maximal 2000 m efforts for both ergometer and on-water (n = 340 of each) were collected from 162 national and international athletes (78 women, 84 men) over 16 years. A linear mixed model predicted on-water performance from static ergometer performance (physiological capability), accounting for day of on-water testing (environmental condition effects). On-water delta was the difference between predicted and actual on-water performance. The model revealed significant fixed effects (intercept = 17.70 s, 95% CI = [8.43, 26.97], p < 0.001; ergometer coefficient = 0.87, 95% CI = [0.81, 0.93], p < 0.001), and random effects for year ranged from -15.43 s to 47.98 s (median = -6.29 s). On-water delta ranged from -32.8 s (faster than predicted) to 51.1 s (slower). On-water delta provides a new dependent variable that can be used to quantify technical ability in future investigations. The current data provide contextual on-water delta values from a large sample of high-level athletes, and the outlined modelling approach can be applied to new datasets to provide population-specific quantifications of technical ability.